2005
DOI: 10.1099/mic.0.27630-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced initiation frequency from oriC restores viability of a temperature-sensitive Escherichia coli replisome mutant

Abstract: The dnaX gene of Escherichia coli encodes t and c clamp loader subunits of the replisome. Cells carrying the temperature-sensitive dnaX2016 mutation were induced for the SOS response at non-permissive temperature. The SOS induction most likely resulted from extensive replication fork collapse that exceeded the cells' capacity for restart. Seven mutations in the dnaA gene that partly suppressed the dnaX2016 temperature sensitivity were isolated and characterized. Each of the mutations caused a single amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 48 publications
(59 reference statements)
3
18
0
Order By: Relevance
“…2d, Table 1). This effect has been previously described by other groups using dnaA defective alleles alone (Gon et al, 2006) or combined with dnaX alleles that impaired the progression of DNA replication (Skovgaard & Løbner-Olesen, 2005).…”
Section: Resultssupporting
confidence: 70%
“…2d, Table 1). This effect has been previously described by other groups using dnaA defective alleles alone (Gon et al, 2006) or combined with dnaX alleles that impaired the progression of DNA replication (Skovgaard & Løbner-Olesen, 2005).…”
Section: Resultssupporting
confidence: 70%
“…According to the model where the RNR is a component of the replication hyperstructure (Guzmán et al, 2002), it is reasonable to think that the defective fork progression observed in this mutant can be alleviated by reducing the number of replication forks running along the chromosome. Consistent with this, the presence of dnaA defective alleles, dnaA(Sx), suppresses the detrimental effect on DNA replication observed in mutants that have problems with the progression of forks due to the presence of defective subunits of DNA polymerase III coded by the dnaX gene (Gines-Candelaria et al, 1995;Blinkova et al, 2003;Skovgaard & Lobner-Olesen 2005). Furthermore, a lower availability of wild type DnaA protein induced by the presence of extra copies of the datA sequence alleviates replication problems in both the dnaX (Skovgaard & Lobner-Olesen, 2005) and the nrdA101 mutant (this work), whilst initiation defects caused by deletion of DnaA box R4 suppress replication elongation defects (Stepankiw et al, 2009).…”
Section: By Deleting the Dars Sequencementioning
confidence: 58%
“…Consistent with this, the presence of dnaA defective alleles, dnaA(Sx), suppresses the detrimental effect on DNA replication observed in mutants that have problems with the progression of forks due to the presence of defective subunits of DNA polymerase III coded by the dnaX gene (Gines-Candelaria et al, 1995;Blinkova et al, 2003;Skovgaard & Lobner-Olesen 2005). Furthermore, a lower availability of wild type DnaA protein induced by the presence of extra copies of the datA sequence alleviates replication problems in both the dnaX (Skovgaard & Lobner-Olesen, 2005) and the nrdA101 mutant (this work), whilst initiation defects caused by deletion of DnaA box R4 suppress replication elongation defects (Stepankiw et al, 2009). These observations, together with our data, are consistent with the idea that the progression of replication forks is not merely responsive to elongation factors (dNTP pools or proteins engaged in elongation) but also to the number of forks running along the chromosome.…”
Section: By Deleting the Dars Sequencementioning
confidence: 58%
See 1 more Smart Citation
“…Determination of the rate of DNA synthesis at any time in an individual cell could lead to breakthroughs in our knowledge of how replication and the cell cycle are coregulated. This might shed some light, for instance, on the suggested reduction of the rate of DNA synthesis at a weakened replicating fork when a second replication round was initiated (Blinkova et al, 2003;Moreno et al, 2013;Salguero et al, 2011;Skovgaard and Løbner-Olesen, 2005). The algorithm should enable determination of the minimal replication rate under thymine limitation in which cell viability is maintained (Zaritsky et al, 2006) and a better description of nucleoid complexity during the cell cycle (Zaritsky, 2015).…”
Section: Results and Conclusionmentioning
confidence: 95%